Unnatural α-amino ethyl esters from diethyl malonate or ethyl β-bromo-α-hydroxyiminocarboxylate - Coutant, Eloi P.; Hervin, Vincent; Gagnot, Glwadys; Ford, Candice; Baatallah, Racha; Janin, Yves L. (Beilstein Journal of Organic Chemistry, 2018)
We have explored here the scope of the age-old diethyl malonate-based accesses to α-amino esters involving Knoevenagel condensations of diethyl malonate on aldehydes, reductions of the resulting alkylidenemalonates, the preparation of the corresponding α-hydroxyimino esters and their final reduction. This synthetic pathway turned out to be general although some unexpected limitations were encountered. The synthetic modifications of some of the intermediates – using Suzuki–Miyaura coupling or cycloadditions – before undertaking the oximation step – provided accesses to further α-amino esters. Moreover, other pathways to α-hydroxyimino esters were explored including an attempt to improve the cycloadditions between ethyl β-bromo-α-hydroxyiminocarboxylate and various alkylfuranes.
Keywords: α-amino ester; α-hydroxyimino ester; [2 + 4] cycloadditions; [2 + 3] cycloadditions; Knoevenagel; nitrosoacrylate; Suzuki–Miyaura